2021
DOI: 10.3389/fphar.2021.593953
|View full text |Cite
|
Sign up to set email alerts
|

β-carotene Rescues Busulfan Disrupted Spermatogenesis Through Elevation in Testicular Antioxidant Capability

Abstract: β-carotene, precursor of vitamin A, is an excellent antioxidant with many beneficial properties. It is a lipid-soluble antioxidant and a very effective quencher of reactive oxygen species (ROS) to reduce the oxidative stress. In contrast to vitamin A, β-carotene is not toxic even consumed in higher amount when it is delivered from natural plant products. Recently, we found that β-carotene acts as a potential antioxidant in the oocyte to improve its quality. Even though many studies have been reported that β-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It has been reported that olive leaf extract, Korean red ginseng, and Genistein can improve spermatogenesis (Chi et al, 2013;Jung et al, 2015;Ganjalikhan Hakemi et al, 2019). Furthermore, we found that alginate oligosaccharides, beta-carotene, and chestnut polysaccharides improved spermatogenesis at various levels (Yu et al, 2020;Zhao et al, 2020;Ma et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
“…It has been reported that olive leaf extract, Korean red ginseng, and Genistein can improve spermatogenesis (Chi et al, 2013;Jung et al, 2015;Ganjalikhan Hakemi et al, 2019). Furthermore, we found that alginate oligosaccharides, beta-carotene, and chestnut polysaccharides improved spermatogenesis at various levels (Yu et al, 2020;Zhao et al, 2020;Ma et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
“…Beta-carotene and other carotenoids are commonly recognized as biological antioxidants. However, the effectiveness of beta-carotene and other carotenoids as antioxidants in disease prevention has been a subject of controversy in clinical studies ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The balance of antioxidants and ROS is essential for many physiological processes including spermatogenesis and sperm maturation [ 44 , 45 ]. Studies have reported that GSH levels decline with aging and are accompanied by elevated oxidative stress in the heart, liver, kidneys, and brain [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%